Coupled flow in groundwater systems : the study of bulkflow parameters - Shakhane, Teboho (University of the Free State, 2011)
This study was aimed at studying bulkflow parameters in groundwater systems at littoral zone of the Modder River. In this thesis, all the aspects were synthesised and exemplified by incorporating a multidisciplinary perspective to develop a sound conceptual framework of the alluvial stream aquifer system. Hydraulic characterisation of the near aquifer system was achieved by acquiring data from a 6-spot pattern well network from which lithological, aquifer hydrogeology, and groundwater hydrogeochemistry characterisations were comprehensively undertaken. The aquifer overburden was estimated to have the permeability of 2.42m/d when its textural classification was found on average to consist of 22% clay+silt and 77% very fine sand. The geology of the study area is typical of the Karoo geology. This was affirmed by massive mudstone bedrock of the Ecca group underlying the study domain. The unconsolidated sediments of gravel, sand and silt, overlie this Karoo mudstone. Therefore, the aquifer is a three units and unconfined alluvial stream aquifer situated in the alluvial deposits along the course of the Modder River. The main units of the system are the upper unit, middle unit and lower aquitard made up of the overbank-fine sand deposits, gravel and mudstone respectively. Groundwater is a bicarbonate type water and falls along a mixing line from sulfatechloride type water to calcium-magnesium type water. This water was found to be both unpolluted sodium enriched and chloride enriched strongly be attributed to forestation of the site where evapotranspiration rates are widespread. Groundwater plots close and parallel to GMWL indicating that recharge is primarily derived from the direct infiltration of precipitation. The δ18O and δD composition of water from the sampled wells indicates that water from all wells drilled in the Riparian or Bank storage aquifer is isotopically lighter than water from wells located on the Terrestrial aquifer. Tritium ranges are indicative of modern water suggesting that the possible influx source might have been precipitation or precipitation derived water. In other words, the groundwater gets recharged with modern rainfalls and has short circulation time in the ground indicative of short travel time. The plot of pH-Tritium indicates that the majority of the samples fall within the rage 6 to 8.5 attributed to recharges with modern and highly neutralised rainfalls. This also suggests short groundwater circulation time in the ground. The groundwater samples with the lowest nitrate concentration were the ones with the lowest tritium level indicating that, although the groundwater source lies on agricultural land, it has not been contaminated by nitrate fertilizers. Groundwater head differences yield the hydraulic gradients from terrestrial aquifer towards riparian aquifer. On average the hydraulic gradient is 0.0083. Flow direction over the entire study domain generally trend SE, sub-perpendicular to the regional surface water flow direction. The EC-profiles show the gravel unit as a major groundwater conduit as shown by a jump in EC values at this unit and this unit is the same water source for all the wells that intercepted the gravel. The transmissivity of the site’s aquifer ranges between 0.3m2/d and 164m2/d. Highest transmissivity estimated at a maximum level are observed in wells located in the riparian aquifer. The unconfined aquifer specific yield is in the order of 0.005- 0.023. Darcy velocity was estimated at 4.16m/d for CYS1BH4 and natural flow velocity for this well was ultimately estimated at 1.81 m/d. On the other hand, Darcy velocity for CYS1BH3 was estimated at 9.01 m/d with natural flow velocity ultimately estimated at 3.92 m/d. Last in the list is CYS1BH5 whose Darcy velocity was estimated at 11.24 m/d and natural flow velocity ultimately estimated at 22.4 m/d. The estimated velocities are relatively high and this observation holds true for transmissivities so high. Baseflow calculations gave a negative value signifying no base flow contribution of groundwater in to the river. This suggests that most groundwater is used up by the riparian vegetation.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2011
Keywords: Groundwater -- South Africa -- Free State -- Measurements; Groundwater -- South Africa -- Free State; Aquifers -- South Africa -- Free State; Hydrogeology; Base flow (Hydrology)